Práticas cotidianas de ensino da língua escrita em classe especial para surdos - Dantas, Mauriza Moura (2006)
This study aimed at checking pedagogic practices used in the process of teaching the written language in special class for deaf pupils. The research was carried out in an elementary school special class, with nine deaf pupils, in a school of the Public Municipal Network that has an explicit schooling policy for these children. For much, data were collected in the academic year of 2005, through video recording of Portuguese Language classes in October, from the material produced by the pupils in the literacy activities developed in classroom and the records of the two-monthly evaluations done by the teacher. Data analysis was carried based on the contributions of Ferreiro (1986 and 1991), in which refers to the distinction between oral language and / or signs language and written language, and of Vygotsky (2002), concerning the interpersonal nature of the initial acquisition of written language, through interactions that must be rich in meanings. In addition to these authors, for the specific field of deaf persons literacy, this study is supported substantially on Soares (1999 and 2004), in addition to Bueno (2001 and 2004). The main findings in the research were: the developed activities took as a principle the perspective of writing as transcription of the signs language; centralizing the teaching of writing through nominations of objects and events; restriction to the copy, when writing does is not presented based on the language of signs or the digital alphabet, indicating that the fact that the pupils copy texts seems, for the teacher, to be sufficient so that they may acquire writing. To the extent that the production of writing was so deprived of its characteristics, on one hand, in terms of appropriation of its basic elements and, on the other hand, by the facilitation of the responses through the transcription of the digital alphabet, where it will be verified that, in fact, the pupil is not being taught to write, but, on the contrary, writing serves more for they to fix and incorporate the language of signs.